Nguyen Van Canh, Vietnam under Communism, 1975-1982, Stanford, California, Hoover Institution Press, Stanford University, 1983, 312 pp. Archimedes L.A. Patti, Why Viet Nam? Prelude to America’s Albatros, Berkeley, University of California Press, 1980, 612 pp. - Connelly, Marisela (Estudios de Asia y África, 1989)
-